DESIGN OF WORK SLOW WIND-WHEEL POWER PLANT WITH PADDLES OF PERMANENT TYPE AFTER ITS RADIUS - Zinko, Roman; Kruts, Taras; Lozovyj, Ihor (International Journal of Computing, 2014)
The task of optimizing velocity rotation of low-speed wind-wheel and optimal profile of its paddles according to criterion at most possible selection of power from weak air flow is set and worked out in the article. The method of determination the necessary angles of own turn of paddles and axis of rotation of wide-wheel shaft with higher speed of air flow with the aim of support nominal capacity of wide-power installation is suggested.